2011
DOI: 10.1016/j.crohns.2011.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Conception and pregnancy outcome in women with inflammatory bowel disease: A multicentre study from Japan

Abstract: In Japanese UC patients, conception and pregnancy outcomes after disease onset were comparable to the outcomes observed prior to disease onset, whereas CD appeared to be associated with adverse outcomes. Caesarean operation and LBW were more frequently observed in CD patients who had a history of surgery for perianal lesions and bowel resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
1
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 27 publications
0
31
1
2
Order By: Relevance
“…Caesarean section was the mode of delivery in 14 of the 43 (33 %) patients in our study; 45 % of the patients in the pancolitis group underwent a Caesarean section as compared to 19 % in group II. Unlike other studies [2,11], our data failed to show a statistically significant higher frequency of Caesarean section in patients with pancolitis but this is likely to be a type II error related to the small sample size. Similarly, disease relapse was more common in the pancolitis group where it was observed in 11 of the 22 (50 %) patients vs. 14 % in group I.…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…Caesarean section was the mode of delivery in 14 of the 43 (33 %) patients in our study; 45 % of the patients in the pancolitis group underwent a Caesarean section as compared to 19 % in group II. Unlike other studies [2,11], our data failed to show a statistically significant higher frequency of Caesarean section in patients with pancolitis but this is likely to be a type II error related to the small sample size. Similarly, disease relapse was more common in the pancolitis group where it was observed in 11 of the 22 (50 %) patients vs. 14 % in group I.…”
Section: Discussioncontrasting
confidence: 83%
“…Thus, the clinical scenario of IBD and pregnancy being present together in a patient is not uncommon. Some studies have shown that IBD is associated with a threefold increase in the risk of preterm delivery and two-to ninefold increase in the risk of low birth weight (LBW) infants [2]. Additionally, a four-to sixfold increase in the fetal growth restriction, i.e.…”
Section: Introductionmentioning
confidence: 98%
“…The risk of congenital abnormalities in the offspring of women suffering from inflammatory bowel disease is the same as in the general population [15,18,20]. In the aforementioned Mahadevan study, the authors did not observe a difference in the congenital malformation rate between women with colitis ulcerosa and Crohn's disease [16].…”
Section: Congenital Malformationsmentioning
confidence: 53%
“…Previous infertility treatment increases the risk of miscarriage. History of intestinal surgery is an independent risk factor for low birth weight or cesarean delivery [15]. Mahadevan et al performed a cohort study comparing obstetric outcomes in IBD and IBD-free patients.…”
Section: Influence On the Course Of Pregnancymentioning
confidence: 99%
“…Those with celiac disease and Crohn's/ulcerative colitis can also have autoimmune responses, which lead to early pregnancy loss. Those with SLE, inflammatory bowel disease, and autoimmune thyroiditis have a statistically significant increased risk of RPL (odds ratio 1.7-5.3) compared to their controls [16][17][18]. Other abnormal labs can place the patient at risk for RPL.…”
Section: Diagnostic Criteria Of Recurrent Pregnancy Lossmentioning
confidence: 99%